Work Values Preferences Of Gen Z In Central Kalimantan - Olivia Winda Ony Panjaitan; Noveria Susijawati; Lisa Harry Sulistiyowati; Nurlia Eka Damayanti (Jurnal Kajian dan Penalaran Ilmu Manajemen, 2023)
This study aimed to confirm Gen Z work values in Central Kalimantan by adapting the instruments and indicators developed by Lyons et al. ( 2010 ), which consist of intrinsic, extrinsic, altruistic, status, and social values. This research is explanatory and descriptive. The research instrument was an online questionnaire. The research respondent were final-year students, with a total of 99 respondents. Data analysis of this study was done by descriptive analysis and independent sample t-test using SPSS 25 software. The result showed that the highest average work values were status-related work values, altruistic work values, and intrinsic work values.